2009
DOI: 10.1175/2009jas3103.1
|View full text |Cite
|
Sign up to set email alerts
|

A Theory for Buoyancy and Velocity Scales in Deep Moist Convection

Abstract: Buoyancy and velocity scales for dry convection in statistical equilibrium were derived in the early twentieth century by Prandtl, but the scaling of convective velocity and buoyancy, as well as the fractional area coverage of convective clouds, is still unresolved for moist convection.In this paper, high-resolution simulations of an atmosphere in radiative-convective equilibrium are performed using the Weather Research and Forecasting (WRF) model, a three-dimensional, nonhydrostatic, convection-resolving, lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 29 publications
8
72
0
Order By: Relevance
“…The sensitivity to fall speed is largest at the highest SST; the 99.99th percentile of vertical velocity increases from roughly 10 to 12 m s −1 at pressure levels near 600 hPa (∼ 5 km) as the fall speed is increased from 1 to 8 m s −1 . This sensitivity to fall speed is smaller than found in the simulations of Parodi and Emanuel (2009). Preliminary investigations indicate that a larger effect of hydrometeor fall speed is found when a simpler, warm-rain microphysics scheme is employed, as was the case in Parodi and Emanuel (2009), and this may be the cause of the discrepancy.…”
Section: Effect Of Changes In Hydrometeor Fall Speedmentioning
confidence: 66%
See 3 more Smart Citations
“…The sensitivity to fall speed is largest at the highest SST; the 99.99th percentile of vertical velocity increases from roughly 10 to 12 m s −1 at pressure levels near 600 hPa (∼ 5 km) as the fall speed is increased from 1 to 8 m s −1 . This sensitivity to fall speed is smaller than found in the simulations of Parodi and Emanuel (2009). Preliminary investigations indicate that a larger effect of hydrometeor fall speed is found when a simpler, warm-rain microphysics scheme is employed, as was the case in Parodi and Emanuel (2009), and this may be the cause of the discrepancy.…”
Section: Effect Of Changes In Hydrometeor Fall Speedmentioning
confidence: 66%
“…This sensitivity to fall speed is smaller than found in the simulations of Parodi and Emanuel (2009). Preliminary investigations indicate that a larger effect of hydrometeor fall speed is found when a simpler, warm-rain microphysics scheme is employed, as was the case in Parodi and Emanuel (2009), and this may be the cause of the discrepancy.…”
Section: Effect Of Changes In Hydrometeor Fall Speedmentioning
confidence: 66%
See 2 more Smart Citations
“…Various CRM studies (e.g. Robe and Emanuel, 1996;Shutts and Gray, 1999;Cohen, 2001;Parodi and Emanuel, 2009) have shown that the strength of the forcing seems to have only a weak effect on the mean mass flux of individual clouds: rather, a change in forcing is associated mainly with a change in the mean number of clouds N . A recent CRM investigation by Davies and Jakob (2011, pers.…”
Section: Theory Of Convective Variabilitymentioning
confidence: 99%